2016
DOI: 10.11648/j.sjbm.20160406.16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Remuneration, Job Satisfaction and OCB on the Employee Performance

Abstract: This study aims to: (1) analyze the effect of remuneration, job satisfaction and Organizational Citizenship Behavior (OCB) on employee performance; (2) analyze the job satisfaction as a mediating variable of the effect remuneration on employee performance; and (3) analyze OCB role in mediating the effect of remuneration and job satisfaction on employee performance. Data was collected using saturated sampling method. The population consisted of 138 Account Representative (AR) Supervision of the work in the Tax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 29 publications
4
35
1
3
Order By: Relevance
“…Basu, Pradhan and Tewari (2017) in their exploration of the relationship between OCB and employee performance through the survey of 501 workers in 15 healthcare organizations in Kolkata in India concluded that OCB significantly predicts job performance in healthcare organizations. Agustiningsih et al (2016) in the survey of 138 Account Representative (AR) Supervision of the work in the Tax Office in Malang area revealed no relationship between OCB and the performance of AR Supervisors. Tehran, Abtahi and Esmaeili (2013) in the study of OCB linkage with the performance of Staff of Qazvin University of Medical Sciences and Health Services reported that OCB dimensions like altruism, work ethics, sportsmanship and civic behaviour positively stimulates employee performance.…”
Section: Literature Review and Hypothesesmentioning
confidence: 97%
“…Basu, Pradhan and Tewari (2017) in their exploration of the relationship between OCB and employee performance through the survey of 501 workers in 15 healthcare organizations in Kolkata in India concluded that OCB significantly predicts job performance in healthcare organizations. Agustiningsih et al (2016) in the survey of 138 Account Representative (AR) Supervision of the work in the Tax Office in Malang area revealed no relationship between OCB and the performance of AR Supervisors. Tehran, Abtahi and Esmaeili (2013) in the study of OCB linkage with the performance of Staff of Qazvin University of Medical Sciences and Health Services reported that OCB dimensions like altruism, work ethics, sportsmanship and civic behaviour positively stimulates employee performance.…”
Section: Literature Review and Hypothesesmentioning
confidence: 97%
“…Paragraph 3: "Remuneration as referred to in paragraph (2) can be given to the Secretary of the Supervisory Board". Agustiningsih, et al (2016) stated that remuneration as financial or non-financial received by employees as a result of performance. The results received are divided into direct and indirect remuneration.…”
Section: Remunerationmentioning
confidence: 99%
“…Many factors influence job performance. According to Agustiningsih et, al (2016), remuneration significantly and negatively affects performance.…”
Section: Introductionmentioning
confidence: 99%
“…OCB involves some elements of behavior such as helping others, volunteering for extra duties, and adhere to the rules and procedures in the workplace. These behaviors are constructive, meaningful and positive social behaviors [15].…”
Section: Organizational Citizenship Behavior (Ocb)mentioning
confidence: 99%